A Knowledge Based System for Managing Heterogeneous Sources of Engineering Information. Issue 2 (2020) - Ocker, Felix; Vogel-Heuser, Birgit; Seitz, Matthias; Paredis, Christiaan J.J.
Abstract: As ever increasing amounts of engineering information become available, engineers require novel ways to manage this information. Especially in mechatronic engineering, e.g., the engineering of Cyber-Physical Production Systems, engineers from various disciplines are involved, and they represent their knowledge in heterogeneous ways. To be able to efficiently gain an overview of the available information and find the information required, engineers need support. Additionally, awareness regarding interdisciplinary dependencies should be increased to reduce late changes. Such dependency analyses allow engineers to better identify and thus manage potential inconsistencies, which can be expected to reduce development time. The Knowledge Based System presented supports engineers during the design process of production systems by providing an overview of available engineering knowledge, its representation, and associated stakeholders. Additionally, engineers can leverage the underlying holistic information model to create and manage digital twins.